Associative experiment as a means of tracking dynamics of secondary language personality development as exemplified by the stimulus word “nation” - Koroleva, Vera Vladimirovna; Polyanskaya, Ekaterina Timofeevna (Этническая культура, 2025)
The article examines the dynamics of secondary language personality formation and the influence of learners’ native linguistic personality on this process. The article reviews the role of associative experiment in linguistic worldview and language personality examination. A chain associative experiment, conducted in three groups with different levels of English proficiency – including a group of native speakers – serves as the primary research method. The lexeme “nation” is used as the stimulus word in the experiment. The interpretation of the results is carried out according to Yu. N. Karaulov’s three-level model of language personality. The findings allow conclusions that there is a strong influence of the native linguistic personality on the formation of the secondary language personality at an early stage of the language mastery and the threshold level (A2–B1). Subjects with a great experience of conscious language acquisition demonstrate the most comprehensive understanding of the stimulus word “nation”, even compared to the native speakers. Furthermore, the prospects of associative experiment application for methodological purposes are noted, particularly for tracking the level of secondary language personality formation in learning groups and adjusting the language learning trajectory.